Determination of Humic Acid in Loess by Potassium Permanganate Oxidization Flow-Injection Chemiluminescence Method - Yang, Shengke; Zhang, Binbin; Zhao, Yue; Chen, Jing (Asian Journal of Chemistry, 2013)
In this study, potassium permanganate was found to be capable of oxidizing humic acid and causing chemiluminescence reaction. The chemiluminescence dynamic curve of KMnO4-humic acid system was drawn, the reaction conditions were optimized and a new chemiluminescence analysis method to determine humic acid in loess was established with the linear range from 1 × 10-1 to 1 × 102 mg/L (R = 0.9989) and detection range of 8 × 10-8 g/mL. Eleven replicate determinations were conducted on humic acid with the concentration of 20 mg/L and the calculated relative standard deviation (RSD) was 2.98 %. By taking the loess from the Loess Plateau as the determination object, the extraction conditions of humic acid from loess were confirmed as follows: the mixture of 0.1 mol/L sodium pyrophosphate and 0.1 mol/L sodium hydroxide was used as extract; the water-soil ratio was 1:30 and the extraction time was 0.5 h. Humic acid in loess obtained from five different regions was determined and standard recovery tests were conducted at the same time, with the standard recovery rate of the samples between 94.0 and 114 %.